Sebaran Nyamuk Pradewasa Berdasarkan Tipe Ekosistem dan Habitat Spesifik di Kabupaten Pandeglang Provinsi Banten - Arda dinata; Endang Puji Astuti; Suwarno Hadisusanto (Loka Litbang Kesehatan Pangandaran, 2020)
Abstract. The vector-borne disease remains a health problem in Pandeglang District. Entomological data is important in the strategy of controlling the vector-borne disease. This study aimed to determine the distribution of mosquito larvae based on specific habitat and ecosystem typea. This research is a secondary data analysis of Rikhus Vektora 2016 in Pandeglang, Banten Province. This type of observational research with cross-sectional study design. The purposive sampling technique is used based on geographical and ecosystem stratification. We found 12 types of environments of the six types of ecosystems (HDP, HJP, NHDP, NHJP, PDP, and PJP) that had larvae: forest (secondary, homogeneous, and coastal); lagoon; brackish water swamp; bamboo clumps; rice fields; plantations; and residential areas. The most ecosystem types were larvae in HJP (160 larvae) and the least larvae in NHDP (9 larvae). Species of larvae are 16 types: rice fields (Cx. vishui, Cx. tritaeniorhynchus, An. barbirostris); small hole in the ground (Anopheles sp., Culex sp.); coconut shell (Ae. albopictus, Ar. malayi, Ar. kuchingensis, Malaya sp, Culex sp.); armpit taro leaves and banana leaves (Ae. albopictus, Malaya genurostris); freshwater swamp (Cx. vishnui, Cx. gelidus) and brackish water (Anopheles sp.); riverside (Anopheles sp., Cx. quinquefasciatus); ditch (Culex sp.); pool (Cx. quinquefasciatus); lagoon (Anopheles sp., Culex sp.); bamboo stumps (Ae. albopictus); Limnocharis flava garden (Culex sp.); and used bottles (Ae. albopictus). The characteristics of larvae habitat: temperature (25-33oC); pH 8-9 (67.3%); light intensity (115-32,000 lux); vegetation (12.7%); algae (3.6%); water is temporary (61.6%), inundated (78.2%) and clear (50,9%). Abstrak. Penyakit tular vektor masih menjadi masalah kesehatan di Kabupaten Pandeglang. Data vektor penting dalam strategi pengendalian penyakit tular vektor. Tujuan penelitian ini untuk mengetahui sebaran jentik nyamuk berdasarkan habitat spesifik dan tipe ekosistem. Penelitian ini merupakan analisa data sekunder Rikhus Vektora 2016 di Kabupaten Pandeglang Provinsi Banten. Jenis penelitian observasional dengan rancangan studi potong lintang. Teknik purposive sampling, digunakan berdasarkan stratifikasi geografis dan ekosistem. Didapatkan 12 jenis lingkungan yang berhasil diidentifikasi dari enam tipe ekosistem (HDP, HJP, NHDP, NHJP, PDP, dan PJP) dengan jentik, yaitu: hutan (sekunder, homogen, pantai); laguna; rawa air payau; rumpun bambu; sawah; perkebunan (salak, pisang, kelapa, kopi); daerah pemukiman. Tipe ekosistem terbanyak jentik di HJP (160 jentik) dan sedikit jentik di NHDP (9 jentik). Habitat spesifik jentik ada 16 jenis, yaitu: sawah (Cx. vishui, Cx. tritaeniorhynchus, An. barbirostris); kobakan (Anopheles sp., Culex sp.); tempurung kelapa (Ae. albopictus, Ar. malayi, Ar. kuchingensis, Malaya sp., Culex sp.); ketiak daun talas dan daun pisang (Ae. albopictus, Malaya genurostris); rawa air tawar (Cx. vishnui, Cx. gelidus) dan air payau (Anopheles sp.); tepi sungai (Anopheles sp., Cx. quinquefasciatus); parit (Culex sp.); kolam (Cx. quinquefasciatus); laguna (Anopheles sp., Culex sp.); tunggul bambu (Ae. albopictus); kebun genjer (Culex sp.); serta botol bekas (Ae. albopictus). Karakteristik habitat jentik pada: suhu (25-33oC); pH 8-9 (67,3%); intensitas cahaya (115-32.000 lux); vegetasi(12,7%); alga (3,6%); air bersifat sementara (61,6%), tergenang (78,2%) dan jernih (50,9%).